Immobilization of lipases on hydrophobic supports: immobilization mechanism, advantages, problems, and solutions - Rodrigues, Rafael C.; Virgen-Ortíz, Jose J.; dos Santos, José C.S.; Berenguer-Murcia, Ángel; Alcantara, Andres R.; Barbosa, Oveimar; Ortiz, Claudia; Fernandez-Lafuente, Roberto (Biotechnology advances, 2019)
Lipases are the most widely used enzymes in biocatalysis, and the most utilized method for enzyme immobilization is using hydrophobic supports at low ionic strength. This method allows the one step immobilization, purification, stabilization, and hyperactivation of lipases, and that is the main cause of their popularity. This review focuses on these lipase immobilization supports. First, the advantages of these supports for lipase immobilization will be presented and the likeliest immobilization mechanism (interfacial activation on the support surface) will be revised. Then, its main shortcoming will be discussed: enzyme desorption under certain conditions (such as high temperature, presence of cosolvents or detergent molecules). Methods to overcome this problem include physical or chemical crosslinking of the immobilized enzyme molecules or using heterofunctional supports. Thus, supports containing hydrophobic acyl chain plus epoxy, glutaraldehyde, ionic, vinylsulfone or glyoxyl groups have been designed. This prevents enzyme desorption and improved enzyme stability, but it may have some limitations, that will be discussed and some additional solutions will be proposed (e.g., chemical amination of the enzyme to have a full covalent enzyme-support reaction). These immobilized lipases may be subject to unfolding and refolding strategies to reactivate inactivated enzymes. Finally, these biocatalysts have been used in new strategies for enzyme coimmobilization, where the most stable enzyme could be reutilized after desorption of the least stable one after its inactivation. •Lipases immobilization on hydrophobic supports via interfacial activation is described in this review•This protocol permits the one step immobilization, purification, stabilization and hyperactivation of lipases•Lipases may be released from the support under certain conditions•Intermolecular crosslinking may prevent enzyme release•Heterofunctional supports prevent enzyme release but they have some limitations•There are many ways of taking full advantage of the new heterofunctional supports